Enhancing simulation environment with TRAFIL - Christos Bouras; Savvas Charalambides; Michalis Drakoulelis; G Kioumourtzis; Kostas Stamos (Simulation Technologies in Networking and Communications: Selecting the Best Tool for the Test, 2014)
This chapter presents TRAFIL, a comprehensive tool for enhancing execution of simulations. It provides an overview of the tool, its architecture and its functionalities. It explains how TRAFIL en-hances the entire simulation procedure including graphical setup of simulation scenarios, automated execution of simulations, flexible handling and storage of simulation trace files and presentation of plots based on processing of simulation results. It presents the concept of metafiles that provides TRAFIL with the flexibility to handle heterogeneous simulation environments. The chapter also compares TRAFIL performance with other similar tools and finds that it offers significantly im-proved performance. It therefore concludes that TRAFIL offers both a rich set of simulation en-hancement functionalities and top performance.